Questionnaire Results (QEP) and the socio-economic problems of students in Higher Education in the time COVID-19 - Sá, Susana Oliveira; Gomes, Carlos Alberto; Sousa, Carlos Meneses (IADITI Editions, 2022)
The gender and economic conditions of students from Higher Education Institutions attending the 1st year, after the COVID-19 pandemic, acquires great importance, especially in terms of study conditions and their emotions. The study, with an international scope and on two continents, aims to use the pandemic questionnaire for students (QEP), with five dimensions under study: conditions for study, emotions, academic performance, teaching strategies and sociability. The QEP was answered by 101 students from a private higher education institution in northern Portugal. The QEP questionnaire is part of a research project that aims to guide specific institutional policies to support students' permanence and completion of courses in Higher Education Institutions, allowing the early identification of intentions to drop out or students at risk. As well as to understand how e-learning teaching influenced teaching, learning and the permanence of students in higher education institutions.
Keywords: e-Learning; Higher Education; COVID-19; Dropout; QEP; Socio-economic environment